Gaya Kepemimpinan Team Leader di Auto2000 Cabang Plaju Palembang - Andi Mukrim Mangga Berani; Mukran Roni (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2026)
This research aims to analyze the leadership style applied by the Team Leader at Auto2000 Plaju Palembang. The background of this research is based on the importance of leadership style in influencing team performance and achieving organizational goals. The method used in this research is qualitative with data collection techniques through observation, interviews, and documentation. The findings reveal that the leadership style applied by the Team Leader tends to be democratic and supportive, characterized by two-way communication, openness to input from team members, and involvement of team members in problem-solving processes. However, in certain situations requiring quick decisions, the Team Leader also applies a more assertive or authoritarian approach. The implementation of leadership functions, including directing through daily briefings and task distribution based on competencies, motivation through praise and support, supervision through work progress monitoring and Standard Operating Procedures, and communication through open and continuous coordination, has been running effectively. The implication of this research is that the application of a democratic leadership style combined with a situational approach has a positive impact on team effectiveness, operational smoothness, employee motivation, and service quality at Auto2000 Plaju Palembang.